2015
DOI: 10.1111/ajt.13095
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Regional Factors of Access to the Renal Transplant Waiting List in France in a Cohort of Dialyzed Patients

Abstract: Several studies have investigated geographical variations in access to renal transplant waiting lists, but none has assessed the impact on these variations of factors at both the patient and geographic levels. The objective of our study was to identify medical and nonmedical factors at both these levels associated with these geographical variations in waiting-list placement in France. We included all incident patients aged 18-80 years in 11 French regions who started dialysis between January 1, 2006, and Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 40 publications
10
46
0
Order By: Relevance
“…These findings are consistent with the few previous French studies [17, 24]. After taking into account age and the clinical characteristics, the chance of being waitlisted was 23% lower for patients in Bretagne than in Ile-de-France.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with the few previous French studies [17, 24]. After taking into account age and the clinical characteristics, the chance of being waitlisted was 23% lower for patients in Bretagne than in Ile-de-France.…”
Section: Discussionsupporting
confidence: 92%
“…A previous study in 11 French regions showed that after taking into account medical and non-medical factors, placement on the list was significantly associated with the region of residence, suggesting waitlisting practice differences [17]. For technical reasons, this study did not include the Ile-de-France region, where 18% of the French population live (INSEE).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing age is regarded as a negative predictor of the access to KT registers. [18,19] In a cross-sectional study of 591 dialysis patients in Budapest, Hungary 325 (71%) of responders received a transplant. Increasing age was associated with decreasing odds of wanting a transplant, and the likelihood of being interested in transplantation was 87% at 18 to 44 years of age, 76% at 45 to 64 years, and 49% at >65 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the United States, United Kingdom, Canada, France and other transplantation jurisdictions have consistently found inequalities in completion of transplant work up and waitlisting for patients on dialysis based on patient factors, including race, gender, socio‐economic status and regional factors. Commentary based on publicly available registry data has questioned the low proportion of prevalent dialysis patients on the renal transplant waitlist in Australia and qualitative analysis of nephrologists’ perspectives on waitlisting has revealed tensions between advocating for the best treatment for their own patients, maintaining professional integrity and protecting centre reputation, and maximizing societal benefit .…”
mentioning
confidence: 99%